Regulation of eosinophilia and allergic airway inflammation by the glycan-binding protein galectin-1 - Ge, Xiao Na (2016)
Galectin-1 (Gal-1), a glycan-binding protein with broad antiinflammatory activities, functions as a proresolving mediator in autoimmune and chronic inflammatory disorders. However, its role in allergic airway inflammation has not yet been elucidated. We evaluated the effects of Gal-1 on eosinophil function and its role in a mouse model of allergic asthma. Allergen exposure resulted in airway recruitment of Gal-1-expressing inflammatory cells, including eosinophils, as well as increased Gal-1 in extracellular spaces in the lungs. In vitro, extracellular Gal-1 exerted divergent effects on eosinophils that were N-glycan- And dose-dependent. At concentrations ≤0.25 μM, Gal-1 increased eosinophil adhesion to vascular cell adhesion molecule-1, caused redistribution of integrin CD49d to the periphery and cell clustering, but inhibited ERK(1/2) activation and eotaxin-1-induced migration. Exposure to concentrations ≥1 μM resulted in ERK(1/2)- dependent apoptosis and disruption of the F- Actin cytoskeleton. At lower concentrations, Gal-1 did not alter expression of adhesion molecules (CD49d, CD18, CD11a, CD11b, L-selectin) or of the chemokine receptor CCR3, but decreased CD49d and CCR3 was observed in eosinophils treated with higher concentrations of this lectin. In vivo, allergen-challenged Gal-1-deficient mice exhibited increased recruitment of eosinophils and CD3+ T lymphocytes in the airways as well as elevated peripheral blood and bone marrow eosinophils relative to corresponding WT mice. Further, these mice had an increased propensity to develop airway hyperresponsiveness and displayed significantly elevated levels of TNF-α in lung tissue. This study suggests that Gal-1 can limit eosinophil recruitment to allergic airways and suppresses airway inflammation by inhibiting cell migration and promoting eosinophil apoptosis.